2008
DOI: 10.1093/mutage/gen008
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for design of the rat comet assay

Abstract: Although the rodent comet assay is gaining acceptance as a standard technique for evaluating DNA damage in vivo, there is no internationally accepted guideline for its conduct and several aspects of its experimental design have not been optimized. For example, no standard positive control is used, there is no agreement on how tissue toxicity should be measured and sources of experimental variability have not been considered in relation to experimental design. This study showed that methylnitrosourea is a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 19 publications
0
36
0
3
Order By: Relevance
“…The latter are thought to represent dead or dying cells severely damaged by cytotoxicity. While ''hedgehogs'' are usually not included in tabulation of comet effects, they may be used as an additional measure of toxic effects (Smith et al, 2008).…”
Section: Significance Of Dna Damage Endpoint Resultsmentioning
confidence: 99%
“…The latter are thought to represent dead or dying cells severely damaged by cytotoxicity. While ''hedgehogs'' are usually not included in tabulation of comet effects, they may be used as an additional measure of toxic effects (Smith et al, 2008).…”
Section: Significance Of Dna Damage Endpoint Resultsmentioning
confidence: 99%
“…For in vivo samples the optimal number of cells scored could be different and recommendations for designing the comet assay with samples from rats, including experimental design issues, have been reported [11]. The comet assay has become an important tool for assessing DNA damage in exposed populations and it is the method of choice for population-based studies of environmental and occupational exposure to pollutants [2].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the use of automated scoring, both with in-house systems and with commercially available equipment [5][6][7][8][9]. However, the impact on the sensitivity of the assay by increasing the number of cells scored has not yet been fully investigated and only a few studies have addressed the issue [6,10,11]. The aim of this study was to investigate if the assay sensitivity could be improved by increasing the number of cells scored in independent samples, compared with the standard number of 100 cells per sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, the procedure was slightly modified according the recommendation of Smith et al (2008). The 100 μl of HMP agarose 0.9% was placed on fully frosted slides.…”
Section: Single Cell Gel Electrophoresis (Comet Assay)mentioning
confidence: 99%